What goes on in digital behaviour change interventions for weight loss maintenance targeting physical activity - Encantado, Jorge (2022)
Funding Information: The authors disclosed receipt of the following financial support for the research, authorship, and/or publication of this article: MMM is funded by a Marie-Sklodowska-Curie (EDGE) Fellowship programme (grant agreement No. 713567). This project has received funding from the European Union’s Horizon 2020 research and innovation programme under grant agreement No. 643309. The material presented and views expressed here are the responsibility of the authors only. Publisher Copyright: © The Author(s) 2022.